Assessment of 3rd Year MBBS and BDS Student’s Knowledge about Hepatitis B Virus and THEIR Attitudes Towards Patient Care in Islam Dental College, Sialkot - Aneela Qaiser, Naveed Inayat, Sana Chaudhry, Nadia Munir, A. Shakeel, Maria Rabbani (Pakistan Journal of Medical & Health Sciences, 2022)
Hepatitis B virus is the most common cause of death in developing country like Pakistan. Most common acute symptoms of this DNA virus are nausea, vomiting, abdominal pain, fatigue and jaundice skin and eyes. Mode of transmission is via blood and its products. Most commonly healthcare workers are the volunteer spreading the virus among the community because of lack of knowledge and improper teaching methodology and assessment methods. Identifying and rectifying the community health issues are very important. BDS and MBBS students’ knowledge must be assessed and measures are needed to improve. Material and methods: Cross sectional study of two months had been conducted in Islam Medical and Dental College Sialkot to assess the knowledge of hepatitis B virus and their attitude towards hepatitis B patient’s care in clinical medical and dental OPD and wards. Close ended questionnaire to assess knowledge and attitude was given. Results: 83 students participated in this study. Mean age of students is 22 years. 41(49.39%) 3rd year BDS students and 42(50.60%) 3rd year MBBS students were included. 61.5% MBBS students had given correct answered about hepatitis B knowledge while 56% BDS students had given correct answered about attitude towards hepatitis B patient care. Conclusion: 3rd year MBBS students have better knowledge of hepatitis B virus than BDS students while BDS students have slightly better attitude towards hepatitis B patient care.